Psychological impact of a country-wide lockdown. Role of personal, behavioral, social, and physical conditions on negative and positive affect and meaning in life - Suárez, Ernesto; Rolo-González, Gladys; Muinos, Gabriel; Chinea-Montesdeoca, Cristina; Duarte-Lores, Isabel; Gil-Giménez, Domingo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
During the early outbreak of COVID-19 in 2020, a strict home lockdown was maintained in Spain for more than 50 days, disrupting social and economic activities. The aim of this study is to explore affective and well-being responses during the initial period of mandatory home lockdown. Specifically, we analyzed: 1) differences in risk perception according to sociodemographic and health profile; 2) relation between social and environmental characteristics of home isolation, positive and negative affect and meaning in life; and 3) the relationship between activities and behaviors performed by people under lockdown and well-being. A total of 1343 Spanish residents participated in this correlational and cross-sectional study. Results show a significant relationship between health and economic risk perception associated with confinement. Higher health risk perception was identified among the older population and those belonging to high-risk groups. High resilience was linked to lower negative affect and greater positive affect and meaning in life. Regarding social and environmental characteristics of home isolation, people living with others reported greater negative affect than people living alone and the daily frequency of use of open-air spaces was linked to positive affect. Higher positive affect and meaning in life were also reported in people who frequently participated in community activities or by helping others. Lower negative affect was only associated with physical exercise.